Implementasi Kurikulum 2013 Terhadap Perkembangan Anak Kelas B di TK Syifaul Qulub Sumberjambe Jember - Umah Amrela (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
The aim of this research is to explain the effect of the 2013 program on B grade children's development at Syifaul Qulub Kindergarten. The first step is for the instructor to attend outreach training and seminars; the second step of the research reveals that the 2013 child development program is implemented in a planning, implementing, and reviewing process. Using a scientific method to develop all future innovations. The third stage is to create enjoyable activities to promote religious moral growth, as well as motor, social mental, cognitive, language, and artistic development.